Resin composition
The resin composition, utilizing epoxy components and inorganic compounds, addresses the cost and strength issues of silane-containing compositions by enhancing adhesion and dispersibility, resulting in high-strength molded products at a lower cost.
Patent Information
- Application Number
- JP2023103385
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-06-23
AI Technical Summary
Existing resin compositions that include silane coupling agents are costly and do not produce molded products with sufficient strength.
A resin composition comprising a base resin, an inorganic compound, and an additive consisting of an epoxy component with a triazine skeleton or an epoxy group-containing acrylic polymer, or a combination with an antioxidant and ester wax, without using silane coupling agents, to enhance strength and dispersibility.
The resin composition achieves molded products with excellent strength and improved adhesion, while being cost-effective due to the use of less expensive epoxy components.
Smart Images

Figure 2025002966000001 
Figure 2025002966000002 
Figure 2025002966000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. [Background technology]
[0002] In resin compositions, additives are used for various purposes. For example, Patent Document 1 describes a resin composition containing two types of polycarbonate resins, which further contains additives such as a flame retardant and a mold release agent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2013-237786 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a resin composition that does not contain a silane coupling agent and that enables the production of molded articles having excellent strength. [Means for solving the problem]
[0005] According to one aspect of the present invention, there is provided a resin composition comprising a base resin, an inorganic compound, and an additive, the additive being an epoxy component consisting of at least one of an epoxy compound having a triazine skeleton and an epoxy group-containing acrylic polymer, or a combination of the epoxy component with at least one of an antioxidant and an ester wax, the total amount of the inorganic compound and the additive being within a range of 1 to 235 parts by mass when the amount of the base resin is taken as 100 parts by mass, and the amount of the additive being within a range of 0.5 to 11 parts by mass when the amount of the inorganic compound is taken as 100 parts by mass.
[0006] According to another aspect of the present invention, there is provided a resin composition comprising a base resin and a composite material, the composite material including an inorganic compound and a surface treatment agent provided on the inorganic compound, the surface treatment agent being an epoxy component consisting of at least one of an epoxy compound having a triazine skeleton and an epoxy group-containing acrylic polymer, or a combination of the epoxy component with at least one of an antioxidant and an ester wax, the amount of the composite material being within a range of 1 to 235 parts by mass when the amount of the base resin is taken as 100 parts by mass, and the amount of the surface treatment agent being within a range of 0.5 to 11 parts by mass when the amount of the inorganic compound is taken as 100 parts by mass.
[0007] According to yet another aspect of the present invention, there is provided a resin composition according to any one of the above aspects, wherein the amount of the epoxy component is 0.1 parts by mass or more when the amount of the inorganic compound is 100 parts by mass.
[0008] According to yet another aspect of the present invention, there is provided the resin composition according to any one of the above aspects, wherein the inorganic compound is one or more selected from the group consisting of wollastonite, mica, talc, calcium carbonate, clay, titanium oxide, aluminum hydroxide, magnesium hydroxide, barium sulfate, and glass. Effect of the Invention
[0009] According to the present invention, there is provided a resin composition which does not contain a silane coupling agent and which enables the production of molded articles having excellent strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present invention will be described. The embodiments described below are more specific embodiments of any of the above aspects. The following items can be incorporated into each of the above aspects alone or in combination.
[0011] <1> First embodiment The resin composition according to the first embodiment of the present invention is a thermoplastic resin composition that can be used to manufacture a molded article. The resin composition according to the first embodiment comprises a base resin, an inorganic compound, and an additive.
[0012] The base resin is, for example, an engineering plastic. Specific examples of the base resin are polycarbonate, polybutylene terephthalate, polyethylene terephthalate, polyamide, and polyacetal. The base resin may be made of one type of compound, or may be a mixture of multiple types of compounds.
[0013] The inorganic compound is dispersed in the base resin and acts, together with the additives, to increase the strength of a molded article made of the resin composition.
[0014] The inorganic compound is preferably one or more selected from the group consisting of wollastonite, mica, talc, calcium carbonate, clay, titanium oxide, aluminum hydroxide, magnesium hydroxide, barium sulfate, and glass. The inorganic compound is included in the resin composition, for example, in the form of particles or fibers. For example, when the inorganic compound is composed of wollastonite, mica, talc, calcium carbonate, clay, titanium oxide, aluminum hydroxide, magnesium hydroxide, or barium sulfate, it is typically included in the resin composition in the form of particles. Also, when the inorganic compound is composed of glass, it is typically included in the resin composition in the form of fibers.
[0015] When the inorganic compound is in the form of particles, the average particle size is preferably in the range of 0.5 to 3000 μm, and more preferably in the range of 1 to 500 μm. Here, the "average particle size" is the median diameter (D50) obtained by a laser diffraction type particle size distribution measuring device.
[0016] When the inorganic compound is in the form of fiber, the average fiber diameter is preferably in the range of 5 to 30 μm, more preferably in the range of 10 to 20 μm. When the inorganic compound is in the form of fiber, the average fiber length is preferably in the range of 1 to 20 mm, more preferably in the range of 3 to 10 mm. Here, the "average fiber diameter" is a diameter obtained, for example, by a digital microscope. Also, the "average fiber length" is a length obtained, for example, by a digital microscope.
[0017] When the amount of the base resin is taken as 100 parts by mass, the total amount of the inorganic compound and the additives is in the range of 1 to 235 parts by mass, preferably in the range of 5 to 100 parts by mass, and more preferably in the range of 11 to 43 parts by mass.
[0018] The additive, together with the inorganic compound, plays a role in increasing the strength of a molded article made of the resin composition.
[0019] The amount of the additive is in the range of 0.5 to 11 parts by mass, and preferably in the range of 1 to 7.5 parts by mass, based on 100 parts by mass of the inorganic compound.
[0020] According to one example, the additive is an epoxy component comprising at least one of an epoxy compound having a triazine skeleton and an epoxy group-containing acrylic polymer. According to another example, the additive is a combination of the above-mentioned epoxy component with at least one of an antioxidant and an ester wax.
[0021] The epoxy component may be an epoxy compound having a triazine skeleton, an epoxy group-containing acrylic polymer, or a combination thereof. When the epoxy component is a combination of an epoxy compound having a triazine skeleton and an epoxy group-containing acrylic polymer, the blending ratio thereof is optional.
[0022] At least a part of the epoxy component bonds with the functional group present on the surface of the inorganic compound within the period from mixing the epoxy component with the inorganic compound to completing molding. As a result, the epoxy component enhances the dispersibility of the inorganic compound in the base resin and inhibits its secondary aggregation. The epoxy component also enhances the adhesion of the inorganic compound to the base resin in the molded product. Furthermore, the epoxy component also inhibits the deterioration of the base resin in the molded product caused by the inorganic compound contacting the base resin. As a result, the physical properties of the molded product are improved. For example, the molded product is less likely to break due to aggregation. Furthermore, the base resin is less likely to deteriorate due to contact with the inorganic compound, and therefore the molded product is less likely to deteriorate.
[0023] Unlike silane coupling agents, epoxy compounds having a triazine skeleton and epoxy group-containing acrylic polymers do not contain silicon atoms, and such compounds are less expensive than silane coupling agents.
[0024] An epoxy compound having a triazine skeleton is, for example, a compound having a structure in which an epoxy group is bonded to one or more nitrogen atoms contained in triazine via a linking group. In one example, the linking group is an alkylene group. In another example, the linking group is a combination of one or more alkylene groups and at least one of an ester bond and an ether bond.
[0025] The epoxy compound having a triazine skeleton may be monofunctional or polyfunctional. When the epoxy compound having a triazine skeleton is polyfunctional, it may be bifunctional, trifunctional, or tetrafunctional or more. When the epoxy compound has tetrafunctional or more, the linking group has a branched structure.
[0026] An example of an epoxy compound having a triazine skeleton is 1,3,5-tris(oxiran-2-ylmethyl)-1,3,5-triazinane-2,4,6-trione.
[0027] The additive may contain only one type of epoxy compound having a triazine skeleton, or may contain multiple types of epoxy compounds having a triazine skeleton.
[0028] The epoxy group-containing acrylic polymer is an acrylic resin having a side chain containing an epoxy group. The epoxy group-containing acrylic polymer may further have a side chain not containing an epoxy group. The epoxy group-containing acrylic polymer is inexpensive compared to a silane coupling agent.
[0029] The epoxy group-containing acrylic polymer has a weight average molecular weight preferably in the range of 5,000 to 200,000, more preferably in the range of 10,000 to 100,000.
[0030] The epoxy group-containing acrylic polymer preferably has an epoxy equivalent in the range of 100 to 5,000, more preferably in the range of 300 to 1,000.
[0031] The proportion of the epoxy component in the additive is preferably 1% by mass or more, and may be 100% by mass.
[0032] The amount of the epoxy component when the amount of the inorganic compound is taken as 100 parts by mass is preferably in the range of 0.1 to 11 parts by mass, more preferably in the range of 1.2 to 2.9 parts by mass. Note that the upper limit of the amount of the epoxy component when the amount of the inorganic compound is taken as 100 parts by mass is the upper limit of the amount of the additive when the amount of the inorganic compound is taken as 100 parts by mass.
[0033] The antioxidant serves to suppress deterioration reactions of the base resin that may occur at the interface between the inorganic compound and the base resin.
[0034] The antioxidant is, for example, one or more of a sulfur-based antioxidant, a phenol-based antioxidant, and a phosphite-based antioxidant.
[0035] The sulfur-based antioxidant may be, for example, one or more of distearyl thiodipropionate and dilauryl thiodipropionate.
[0036] The phenolic antioxidant is, for example, one or more of pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate] and n-octadecyl 3-(4'-hydroxy-3',5'-di-tert-butylphenyl)propionate.
[0037] An example of the phosphite antioxidant is tris(2,4-di-tert-butylphenyl)phosphite.
[0038] The proportion of the antioxidant in the additives is preferably 50% by mass or less, and more preferably 20% by mass or less, and may be 0% by mass.
[0039] The ester wax enhances the dispersibility of the inorganic compound in the base resin through the molten wax component, suppressing secondary aggregation, and also suppresses shear heat generation through its lubricating effect, thereby suppressing decomposition of the base resin.
[0040] The ester wax is, for example, an ester bond formed between a long-chain fatty acid having a carbon atom number in the range of 12 to 22 and a polyhydric alcohol having a valence number in the range of 2 to 6. The melting point of the ester wax is, for example, in the range of 50 to 100°C.
[0041] Specific examples of the ester wax include glycerin monostearate, glycerin distearate, glycerin tristearate, glycerin tri-12 hydroxystearate, and pentaerythritol tetrastearate.
[0042] The proportion of the ester wax in the additive is preferably 50% by mass or less, more preferably 44% by mass or less, and may be 0% by mass.
[0043] This resin composition can be obtained, for example, by mixing an inorganic compound and an additive, and kneading this mixture with a base resin.
[0044] <2> Second embodiment The resin composition according to the second embodiment of the present invention is a thermoplastic resin composition that can be used to manufacture a molded product. The resin composition according to the second embodiment is composed of a base resin and a composite material. The base resin is the same as that described in the first embodiment.
[0045] The composite material includes an inorganic compound and a surface treatment agent.
[0046] The inorganic compound is the same as that described in the first embodiment. In addition, the amount of the composite material when the amount of the base resin is taken as 100 parts by mass is also the same as the total amount of the inorganic compound and the additives described in the first embodiment.
[0047] The surface treatment agent is provided on the inorganic compound. The surface treatment agent is the additive described in the first embodiment.
[0048] The amounts of the surface treatment agent and its components are the same as those of the additives and its components described in the first embodiment. That is, the amount of the surface treatment agent when the amount of the inorganic compound is 100 parts by mass is the same as the amount of the additives when the amount of the inorganic compound is 100 parts by mass described in the first embodiment. The ratio of each component in the surface treatment agent is the same as the ratio of each component in the additives described in the first embodiment. Furthermore, the amount of the epoxy component when the amount of the inorganic compound is 100 parts by mass is the same as the amount described in the first embodiment.
[0049] This resin composition can be obtained, for example, by mixing the inorganic compound and the surface treatment agent under heating, adding this mixture to the base resin, and kneading.
[0050] <3> effect By using the resin composition according to the first or second embodiment, a molded article having excellent strength can be produced at low cost, as will be described below.
[0051] When an inorganic compound is used in a thermoplastic resin composition used to manufacture a molded article, the inorganic compound may be surface-treated with a silane coupling agent or stearic acid. However, since silane coupling agents are expensive, when a silane coupling agent is used as a surface treatment agent, the resin composition is also expensive. On the other hand, stearic acid is inexpensive, but when molding at high temperatures, molded articles manufactured from a resin composition using stearic acid as a surface treatment agent tend to have inferior performance compared to molded articles manufactured from a resin composition using a silane coupling agent as a surface treatment agent.
[0052] The epoxy component is inexpensive compared to a silane coupling agent. The epoxy component is excellent in heat resistance and can be bonded to an inorganic compound. Therefore, by using the resin composition according to the first or second embodiment, a molded product having excellent strength can be produced inexpensively, as described below.
[0053] As described above, the epoxy component can bond with the functional groups present on the surface of the inorganic compound within the period from mixing the epoxy component with the inorganic compound to completing molding. Therefore, the epoxy component may be applied to the inorganic compound as a surface treatment agent or a part thereof, or may be contained in the resin composition as an additive or a part thereof. EXAMPLES
[0054] Tests carried out in relation to the present invention are described below.
[0055] (1) Test A (1.1) Production of resin composition Resin compositions according to Samples 1 to 25 were produced according to the formulations shown in Tables 1 to 3.
[0056] Specifically, polycarbonate was used as the base resin, and the proportion of the base resin in the resin composition was 85 mass %.
[0057] Wollastonite having an average particle size of 3.3 μm was used as the inorganic compound. The total ratio of the inorganic compound and the surface treatment agent or additives to the resin composition was 15 mass %.
[0058] In the resin compositions according to Samples 1 to 25, the amount of the surface treatment agent or additive based on the inorganic compound and the composition of the surface treatment agent or additive were changed as shown in Tables 1 to 3. Here, in Tables 1 to 3, the numerical values in the column labeled "Surface treatment agent / additive (mass %)" indicate the proportion of each component in the surface treatment agent or additive.
[0059] Sample 1 was produced by kneading the base resin and the inorganic compound. Other parts of Samples 2 to 25 were produced by heating and mixing the inorganic compound and the surface treatment agent, coating the inorganic compound with the surface treatment agent, and then kneading this composite with the base resin. The remaining parts of Samples 2 to 25 were produced by mixing the inorganic compound and the additives, and kneading this mixture with the base resin. In Tables 1 to 3, for samples that used a surface treatment agent or additive, the production method is indicated by "surface treatment" or "addition" in the "treatment" column.
[0060] (1.2) Evaluation (1.2.1) Charpy impact test Using a twin-screw extruder, pellets were produced from each of the resin compositions according to Samples 1 to 25. Next, using an injection molding machine, a molded article was produced from the pellets.
[0061] Then, test pieces were obtained from each molded product, and the Charpy impact strength was measured according to JIS K 7111:2012. The test conditions were JIS K7111-1 / 1eA. The hammer weight was 2J.
[0062] The Charpy impact values obtained for Samples 1 to 25 were evaluated according to the following criteria. 1: Charpy impact value is 1kJ / m 2 below. 2: Charpy impact value is 1.1 to 2 kJ / m 2 . 3: Charpy impact value is 2.1 to 3 kJ / m 2 . 4: Charpy impact value is 3.1 to 4 kJ / m 2 . 5: Charpy impact value is 4.1 kJ / m 2 The end.
[0063] (1.2.2) Bending test Using a twin-screw extruder, pellets were produced from each of the resin compositions according to Samples 1 to 25. Next, using an injection molding machine, a molded article was produced from the pellets.
[0064] Then, test pieces were obtained from each molded product, and bending strength was measured according to JIS K 7171: 2022. The test pieces were type B1 as specified in JIS K 7139: 2009. The test speed was 10 mm / min.
[0065] The maximum stress obtained for Samples 1 to 25 was evaluated according to the following criteria: 1: Maximum stress is 30MPa or less. 2: Maximum stress is 30.1 to 60 MPa. 3: Maximum stress is 60.1 to 90 MPa. 4: Maximum stress is 90.1 to 120 MPa. 5: Maximum stress is 120.1 MPa or more.
[0066] In addition, the percentage of the 10 test pieces that reached the yield point without breaking was evaluated based on the following criteria to evaluate the yield point arrival, which is an index of the resistance to breakage due to bending and tension. 1: The ratio is between 0 / 10 and 2 / 10. 2: The ratio is between 3 / 10 and 4 / 10. 3: The ratio is between 5 / 10 and 6 / 10. 4: The ratio is between 7 / 10 and 8 / 10. 5: The ratio is between 9 / 10 and 10 / 10.
[0067] (1.2.3) Tensile test Using a twin-screw extruder, pellets were produced from each of the resin compositions according to Samples 1 to 25. Next, using an injection molding machine, a molded article was produced from the pellets.
[0068] Then, test pieces were obtained from each molded product, and the tensile strength and elongation were measured according to JIS K7161-1: 2014. The test pieces were 1A type as specified in JIS K7161-2: 2014. The test speed was 20 mm / min.
[0069] The maximum stress obtained for Samples 1 to 25 was evaluated according to the following criteria: 1: Maximum stress is 15MPa or less. 2: Maximum stress is 15.1 to 30 MPa. 3: Maximum stress is 30.1 to 45 MPa. 4: Maximum stress is 45.1 to 60 MPa. 5: Maximum stress is 60.1 MPa or more.
[0070] The elongation obtained for Samples 1 to 25 was evaluated according to the following criteria. 1: Elongation rate is less than 3%. 2: Elongation rate is 3.1 to 6%. 3: Elongation rate is 6.1 to 9%. 4: Elongation rate is 9.1 to 12%. 5: Growth rate is 12.1% or more.
[0071] (1.2.4) MVR (Melt Volume Flow Rate) Test The MVR value of each of the resin compositions according to Samples 1 to 25 was measured in accordance with JIS K 7210-1:2014. The test temperature was 250°C and the test load was 30 kgf / cm 2 The MVR value thus obtained was used to evaluate the deterioration of the resin according to the following criteria. 1: MVR value is 300.1 cm 3 / More than 10 minutes. 2: MVR value is between 225.1 and 300 cm 3 / 10 minutes. 3: MVR value is between 150.1 and 225 cm 3 / 10 minutes. 4: MVR value is between 75.1 and 150 cm 3 / 10 minutes. 5: MVR value is 75cm 3 / 10 minutes or less.
[0072] (1.2.5) Overall Judgment The above scores were summed up for each sample, and the total score was compared with the following criteria to make an overall judgment. 1: The total value is 11 or less. 2: Sum between 12 and 17. 3: Sum between 18 and 23. 4: Sum is between 24 and 29. 5: Total value is 30 or more.
[0073] The above results are shown in Tables 1 to 3.
[0074] [Table 1]
[0075] [Table 2]
[0076] [Table 3]
[0077] The resin composition of Sample 1 was produced without using any surface treatment agent or additive. The resin compositions of Samples 4 and 16 to 25 were produced without using any surface treatment agent or additive, and did not contain any silane coupling agent or epoxy component, or contained any component other than the silane coupling agent, epoxy component, antioxidant, and ester wax. As shown in Tables 1 to 3, the resin compositions of Samples 1, 4, and 16 to 25 achieved a rating of 3 or less in the overall evaluation.
[0078] In contrast, the resin compositions according to Samples 5 to 15 have a surface treatment agent or additive that is composed of an epoxy component, or an epoxy component and at least one of an antioxidant and an ester wax. As shown in Tables 1 to 3, the resin compositions according to Samples 5 to 15 achieved a rating of 4 or higher in the overall evaluation, similar to the resin compositions according to Samples 2 and 3 that contained a silane coupling agent.
[0079] (2) Test B (2.1) Preparation of resin composition Resin compositions according to Samples 26 to 37 were produced according to the formulations shown in Tables 4 and 5.
[0080] Specifically, polycarbonate was used as the base resin, and the proportion of the base resin in the resin composition was 85 mass %.
[0081] Wollastonite having an average particle size of 3.3 μm was used as the inorganic compound. The total ratio of the inorganic compound and the surface treatment agent or additives to the resin composition was 15 mass %.
[0082] In the resin compositions according to Samples 26 to 37, the amount of the surface treatment agent or additive based on the inorganic compound was changed as shown in Tables 4 and 5.
[0083] Some of Samples 26 to 37 were produced by heating and mixing an inorganic compound and a surface treatment agent, coating the inorganic compound with the surface treatment agent, and then kneading this composite with a base resin. The rest of Samples 26 to 37 were produced by mixing an inorganic compound and an additive, and kneading this mixture with a base resin. In Tables 4 and 5, samples that used a surface treatment agent or additive are shown in the "Treatment" column as "Surface Treatment" or "Addition," indicating the production method.
[0084] (2.2) Evaluation Each of the resin compositions according to Samples 26 to 37 was evaluated in the same manner as in Test A. The results are shown in Tables 4 and 5. Tables 4 and 5 also show the results obtained for the resin compositions according to Samples 5 and 6, respectively.
[0085] [Table 4]
[0086] [Table 5]
[0087] In the resin compositions of Samples 5, 6, and 26 to 37, the surface treatment agent or additive comprises an epoxy component, an antioxidant, and an ester wax. When the amount of the surface treatment agent or additive based on the inorganic compound was within the range of 0.5 to 10 mass%, that is, when the amount of the surface treatment agent or additive was within the range of 0.5 to 11 mass parts per 100 mass parts of the inorganic compound, the overall evaluation was rated at 4 or higher. In contrast, when the amount of the surface treatment agent or additive based on the inorganic compound was reduced or increased, the overall evaluation was rated at 3.
[0088] (3) Test C (3.1) Preparation of resin composition Resin compositions of Samples 38 to 49 were produced according to the formulations shown in Tables 6 and 7.
[0089] Specifically, polycarbonate was used as the base resin, and the proportion of the base resin in the resin composition was 85 mass %.
[0090] As the inorganic compound, mica, talc, calcium carbonate or glass fiber was used. The average particle size of the mica was 27 μm. The average particle size of the talc was 4.0 μm. The average particle size of the calcium carbonate was 1.8 μm. The average fiber diameter of the glass fiber was 10 μm and the average fiber length was 4.5 mm. The total ratio of the inorganic compound and the surface treatment agent or additive to the resin composition was 15 mass %.
[0091] In the resin compositions of Samples 38 to 49, the amount of the surface treatment agent or additive based on the inorganic compound and the composition of the surface treatment agent or additive were changed as shown in Tables 6 and 7.
[0092] Some of Samples 38 to 49 were produced by kneading the base resin and the inorganic compound. Others of Samples 38 to 49 were produced by heating and mixing the inorganic compound and the surface treatment agent, coating the inorganic compound with the surface treatment agent, and then kneading this composite with the base resin. The rest of Samples 38 to 49 were produced by mixing the inorganic compound and the additive, and kneading this mixture with the base resin. In Tables 6 and 7, for samples that used a surface treatment agent or additive, the production method is indicated by "surface treatment" or "addition" in the "treatment" column.
[0093] (3.2) Evaluation Each of the resin compositions according to Samples 38 to 49 was evaluated in the same manner as in Test A. The results are shown in Tables 6 and 7.
[0094] [Table 6]
[0095] [Table 7]
[0096] As shown in Tables 6 and 7, when mica, talc, calcium carbonate or glass fiber was used as the inorganic compound, a high rating in the overall assessment was achieved by using a surface treatment agent or additive having a specified composition, just as when wollastonite was used as the inorganic compound.
Claims
1. The composition comprises a base resin, an inorganic compound, and an additive, the additive is an epoxy component comprising at least one of an epoxy compound having a triazine skeleton and an epoxy group-containing acrylic polymer, or a combination of the epoxy component with at least one of an antioxidant and an ester wax; the total amount of the inorganic compound and the additive is in the range of 1 to 235 parts by mass when the amount of the base resin is 100 parts by mass; The amount of the additive is in the range of 0.5 to 11 parts by mass when the amount of the inorganic compound is taken as 100 parts by mass.
2. It consists of a base resin and a composite material, The composite material includes an inorganic compound and a surface treatment agent provided on the inorganic compound, the surface treatment agent is an epoxy component comprising at least one of an epoxy compound having a triazine skeleton and an epoxy group-containing acrylic polymer, or a combination of the epoxy component with at least one of an antioxidant and an ester wax, the amount of the composite material is in the range of 1 to 235 parts by mass per 100 parts by mass of the base resin; The amount of the surface treatment agent is in the range of 0.5 to 11 parts by mass when the amount of the inorganic compound is taken as 100 parts by mass.
3. 3. The resin composition according to claim 1, wherein the amount of the epoxy component is 0.1 parts by mass or more when the amount of the inorganic compound is 100 parts by mass.
4. The resin composition according to claim 1 or 2, wherein the inorganic compound is at least one selected from the group consisting of wollastonite, mica, talc, calcium carbonate, clay, titanium oxide, aluminum hydroxide, magnesium hydroxide, barium sulfate and glass.
Citation Information
Patent Citations
Polyphenylene sulfide resin composition
JP2006104222A
Resin composition and molded article comprising the same
WO2010084845A1
Polycarbonate resin composition
JP2013237786A